Answer:
-1/11 (fraction)
Explanation:
Start by distributing the negative and the three to the numbers in the parenthesis. So that you would get -2x-x+2=5x+3x+3
Then you would combine like terms. -2x -1x= -3x
and 5x+ 3x= 8x
-3x+2=8x+3
After you could either subtract 8x and move it to the other side of the the equal sign or add 3x to 8x. And do the same for 2 and 3. That would leave you with -1=11x which then you divide by 11 so that would get you -1/11
-2x-(x-2)=5x+3(x+1)
-2x-1x+2=5x+3x+3
-3x+2=8x+3
+3x +3x
2= 11x+3
-3 -3
-1=11x